Human-Animal Relationships from the Perspective of Deleuze-Guattari: Ecocriticism Approach to Short Stories in Kompas.id - Fadhilla, Indah; Aminullah, Zakariya Pamuji; Wahyunengsih, Wahyunengsih (Aksara, 2025)
This study aims to analyse the transformation of animal narratives in short stories published in Kompas.id between 2020 and 2023, with a focus on the relationship between humans and animals. Animal stories, which were previously positioned as a medium for moral education for children in Indonesia, have now developed into a medium for criticising the relationship between humans, animals, and the environment. Data was collected through a literature study by searching and archiving animal-themed short stories published in Kompas.id during the period. The data analysis technique used was textual analysis with a philosophical interpretation, using Deleuze and Guattari's theory, particularly the concepts of becoming-animal and Body without Organs (BwO). This study analyses five short stories, namely Macan (2020), Histeinalbtraum (2020), Riwayat Seekor Babi (2021), Monyet Pemetik Teh (2022), and Doa Burung-burung (2022). These short stories depict the transformation of animal narratives through allegories laden with social and political meanings. This study reveals the complex dynamics in human-animal relations, while challenging social norms and hierarchies in Indonesian literature. The findings of this study offer a new reading of animal narratives as a medium of ecological criticism that exposes social, cultural, and political tensions in the context of contemporary literature. AbstrakPenelitian ini bertujuan menganalisis transformasi narasi binatang dalam cerpen-cerpen yang dipublikasikan di Kompas.id antara tahun 2020 hingga 2023, dengan fokus pada relasi manusia dan hewan. Kisahan binatang yang sebelumnya diposisikan sebagai media pendidikan moral bagi anak-anak di Indonesia kini berkembang menjadi medium kritik terhadap relasi manusia, hewan, dan lingkungan. Data dikumpulkan melalui studi pustaka dengan menelusuri dan mengarsipkan cerpen-cerpen bertema binatang yang diterbitkan di Kompas.id selama periode tersebut. Teknik analisis data yang digunakan adalah analisis tekstual dengan interpretasi filosofis, menggunakan teori Deleuze dan Guattari, khususnya konsep becoming-animal dan Body without Organs (BwO). Penelitian ini menganalisis lima cerpen yaitu Macan (2020), Histeinalbtraum (2020), Riwayat Seekor Babi (2021), Monyet Pemetik Teh (2022), dan Doa Burung-burung (2022). Cerpen ini menggambarkan transformasi narasi binatang melalui alegori yang sarat muatan sosial dan politik. Penelitian ini mengungkap dinamika kompleks dalam relasi manusia-hewan, sekaligus menantang norma-norma sosial dan hierarki dalam sastra Indonesia. Temuan penelitian ini menawarkan pembacaan baru atas narasi binatang sebagai medium kritik ekologis yang menyingkap ketegangan sosial, budaya, dan politik dalam konteks sastra kontemporer.